PENGARUH PENGIMPLEMENTASIAN CORPORATE GOVERNANCE TERHADAP PERINGKAT SURAT UTANG PERUSAHAAN JASA GO PUBLIC DI INDONESIA (Studi kasus pada pada perusahaan jasa go public di indonesia tahun 2014) - Maurit, Paul; Mardiati, Endang (Jurnal Ilmiah Mahasiswa FEB, 2014)
The aim of this research is to give empirical evidence of the effect of corporate governance on firm’s bond rating in Indonesia. This research refers to the former research conducted by Bennedick (2008). The sample of this research is 30 firms which came from the firms that issued bond and listed per December 31st 2014 on PT. Bursa Efek Indonesia. The hypothesis testing is using logistic regression with α=5% because dependent variable is a nominal (category). The dependent variable is the bond rating that issued by PT. Pefindo Credit Rating Indonesia which could be accessed from www.pefindo.com, www.idx.co.id and Indonesian Capital Market Directory. The analysis of this research is using SPSS 15 for Windows computer program. The result of this research found that the firm’s bond rating is positively related with ownership structure (institutional ownership). Using the Audit Committee proxy, this research   found   that   firm’s   bond   rating   positively   related   with   the   financial transparency and disclosure. And the test of board structure using the percentage of board independent could found a significant effect on firm’s bond rating.   Keyword: corporate governance, bond rating, logistic regression, ownership structure, financial transparency and disclosure, board structure